Problems of transition to energy-saving management - Holubtsov, M. V.; Fedorov, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The problems of management of the processes of transition of the energy supply and energy consumption systems to the energy-saving functioning are considered on the example of electric illumination. It is shown that transitional process must be optimized and guided.